Analisis Waktu Bongkar Muat Petikemas Pada Alat Ship To Shore (STS) Crane Di Terminal Teluk Lamong - Ashury Ashury; Jessica Indah Pricilla (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2020)
Every year the use of containers is increasing. The loading and unloading problem at the container terminal is often the object of review regarding its performance. This study analyzes the performance of the service system at the Teluk Lamong Terminal which emphasizes the Ship to Shore (STS) crane facility with the formulation of the problem of how the movement time of the STS tool Crane in handling container loading and unloading and whether the container loading and unloading service on the STS Crane is operating optimally. The purpose of this study was to determine the time of loading and unloading of containers and the performance of the Ship to Shore (STS) crane at Lamong Bay Terminal. This research uses a descriptive method. The data source used is primary data taken by observing, interviewing, and measuring directly the service time of the STS tool Crane with a duration of ± 1 hour. Secondary data is obtained by quoting documents from the relevant agencies such as data on the number of equipment facilities, the capacity of tools, age of tools, and layout of Teluk Lamong Terminal. The results of the analysis show that the performance of the Ship to Shore (STS) crane service time is quite good. This can be seen from the highest STS Crane service is STS 04D at loading process of 25 boxes/STS/hour, while theSTSservice Crane lowest STS 03I at 18 boxes/STS/hour loading process. Based on the data, it is concluded that the performance of the Ship to Shore (STS) crane service time can still be improved, so that the production capacity reaches a maximum.